The limits of democratic governance in South Africa - Picard, Louis A.; Mogale, Thomas (Lynne Rienner Publishers, 2015)
In the transition from apartheid rule to democratic governance in South Africa, what has been the impact on South African society at its base - on the people in the country's cities, towns, villages, and farms? Louis Picard and Thomas Mogale offer answers to this fundamental question, tracing historical trends and measuring change (or the lack of it) in the dynamic between the promise of local participatory governance and the realities of a hierarchical state.